A comparative study of microstructure and corrosion resistance in DP980 steel joints under different laser welding method - Shengli Liu; Taotao Li; Ruifeng Li; Kai Qi; Zhenguang Liu (Journal of Materials Research and Technology, 2023)
Three different laser welding methods were used to welding 2 mm DP980 steel butt joint, which were laser welding, laser-TIG hybrid welding and laser powder feeding (CoCrNi) welding respectively. An observational analysis was carried out in terms of microstructure, mechanical properties and corrosion resistance. It was discovered that a central microstructure of laser welding and laser-TIG hybrid welding the weld was dominated by slatted martensite. The laser powder feeding welding has resulted in a remarkable reduction of cylindrical crystals and an increased number of isometric crystals in weld center due to the addition of CoCrNi powder. Microstructure was further refined in incomplete phase transition zone by three different laser welding methods. The tempered martensite was also formed in the tempering zone, which softened the joint. The hardness values decreased considerably and tensile samples were also fractured at this location. Comparison with corrosion resistance of their joints through polarization curves and impedance spectra shows that laser powder feeding joint > laser joint > laser-TIG hybrid joint. The corrosion resistance of laser and laser-TIG hybrid joints in the base metal (BM) > heat affected zone (HAZ) > weld zone (WZ) is shown based on scanning vibrating electrode technique (SVET) localized area testing data at different time intervals. The laser powder feeding welding enhances the density of passivation film by reacting Cr to form Cr2O3, thereby improving corrosion resistance of entire joint.